Alternative futures for Borneo show the value of integrating economic and conservation targets across borders - Runting, R.K.; Meijaard, E.; Abram, N.K.; Wells, J.A.; Gaveau, D.L.A.; Ancrenaz, M.; Possingham, H.P.; Wich, S.A.; Ardiansyah, F.; Gumal, M.T.; Ambu, L.N.; Wilson, K.A. (Springer, 2015)
Balancing economic development with international commitments to protect biodiversity is a global challenge. Achieving this balance requires an understanding of the possible consequences of alternative future scenarios for a range of stakeholders. We employ an integrated economic and environmental planning approach to evaluate four alternative futures for the mega-diverse island of Borneo. We show what could be achieved if the three national jurisdictions of Borneo coordinate efforts to achieve their public policy targets and allow a partial reallocation of planned land uses. We reveal the potential for Borneo to simultaneously retain ∼50% of its land as forests, protect adequate habitat for the Bornean orangutan (Pongo pygmaeus) and Bornean elephant (Elephas maximus borneensis), and achieve an opportunity cost saving of over US$43 billion. Such coordination would depend on enhanced information sharing and reforms to land-use planning, which could be supported by the increasingly international nature of economies and conservation efforts.